2020
DOI: 10.3390/molecules25194442
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Pretreatment Induces Endoplasmic Reticulum Stress-Mediated Hormesis and Attenuates Cisplatin-Induced Oxidative Stress and Damage in LLC-PK1 Cells

Abstract: Isoliquiritigenin (IsoLQ) is a flavonoid with antioxidant properties and inducer of endoplasmic reticulum (ER) stress. In vitro and in vivo studies show that ER stress-mediated hormesis is cytoprotective; therefore, natural antioxidants and ER stress inducers have been used to prevent renal injury. Oxidative stress and ER stress are some of the mechanisms of damage involved in cisplatin (CP)-induced nephrotoxicity. This study aims to explore whether IsoLQ pretreatment induces ER stress and produces hormesis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 94 publications
(187 reference statements)
1
15
0
Order By: Relevance
“…Based on the above findings and ISO has been reported to improve oxidative stress (Alzahrani et al, 2020;G omez-Sierra, Medina-Campos, Solano, Ibarra-Rubio, & Pedraza-Chaverri, 2020) Consistent with these data, mice treated with ISO also displayed elevated expression of fatty acid oxidation-related proteins but reduced expression of proteins related to lipid synthesis (Figure 3F-H, Data S1). Taken together, these data demonstrate that ISO reduced intracellular lipid content by reducing lipid synthesis and increasing lipid oxidation processes.…”
Section: Iso Impeded Intracellular Lipid Content Via Pparα and Srebp1 Inductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Based on the above findings and ISO has been reported to improve oxidative stress (Alzahrani et al, 2020;G omez-Sierra, Medina-Campos, Solano, Ibarra-Rubio, & Pedraza-Chaverri, 2020) Consistent with these data, mice treated with ISO also displayed elevated expression of fatty acid oxidation-related proteins but reduced expression of proteins related to lipid synthesis (Figure 3F-H, Data S1). Taken together, these data demonstrate that ISO reduced intracellular lipid content by reducing lipid synthesis and increasing lipid oxidation processes.…”
Section: Iso Impeded Intracellular Lipid Content Via Pparα and Srebp1 Inductionsupporting
confidence: 81%
“…Based on the above findings and ISO has been reported to improve oxidative stress (Alzahrani et al, 2020; Gómez‐Sierra, Medina‐Campos, Solano, Ibarra‐Rubio, & Pedraza‐Chaverri, 2020), we next explored how ISO lowered lipid content in hepatocytes. First, we measured mitochondrial function using the Seahorse XF Cell Mito Stress Test kit.…”
Section: Resultsmentioning
confidence: 92%
“…Isoliquiritigenin (IsoLQ) is a flavonoid with antioxidant properties and is an inducer of ER stress. It was shown that IsoLQ pretreatment of a kidney cell line induced ER stress-mediated hormesis [ 60 ]. Other agents inducing a hormetic dose response are chloroquine [ 61 ] and green tea with its principal constituent (-)-epigallocatechin-3-gallate (EGCG) [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cisplatin treatment decreased the GSH/GSSG ratio, which was significantly reversed by 6-shogaol. A decrease in the GSH/GSSG ratio indicates increased oxidative stress [ 39 , 40 ]. Altogether, our data indicates that 6-shogaol exhibited an anti-oxidative effect in cisplatin-induced AKI.…”
Section: Discussionmentioning
confidence: 99%